The city and urban studies in Perú: A historical and bibliographical revision within power relations - Evans Morales, Franco Antunez (2019)
This article seeks to analyze the physical and urban changes of the city in Peru within the metropolitan context through an interdisciplinary perspective that takes into account the history and urban studies. Therefore, it is divided into two sections: the first one makes an X-ray of the Peruvian city from the Colony, the Republic, going through the nineteenth century to the context of the twentieth century; The second section presents a brief summary of the urban studies on the city carried out in Peru from the 1950s to the early 1990s, from different disciplines of the social sciences. For this, an exhaustive bibliographical reading of the most important academic productions of the country was carried out, the results show that the city has changed within its urban structure, going from being a compact city in the Colony to a fragmented city in the neoliberal era, of the In the same way, urban studies in Peru have addressed new issues, moving from housing and slum studies to issues such as youth subcultures and new urban identities.